Delivery of the Radionuclide (131)I Using Cationic Fusogenic Liposomes as Nanocarriers - Kolašinac, Rejhana (Int J Mol Sci, 2021)
Liposomes are highly biocompatible and versatile drug carriers with an increasing number of applications in the field of nuclear medicine and diagnostics. So far, only negatively charged liposomes with intercalated radiometals, e.g., (64)Cu, (99m)Tc, have been reported. However, the process of cellular uptake of liposomes by endocytosis is rather slow. Cellular uptake can be accelerated by recently developed cationic liposomes, which exhibit extraordinarily high membrane fusion ability. The aim of the present study was the development of the formulation and the characterization of such cationic fusogenic liposomes with intercalated radioactive [(131)I]I(−) for potential use in therapeutic applications. The epithelial human breast cancer cell line MDA-MB-231 was used as a model for invasive cancer cells and cellular uptake of [(131)I]I(−) was monitored in vitro. Delivery efficiencies of cationic and neutral liposomes were compared with uptake of free iodide. The best cargo delivery efficiency (~10%) was achieved using cationic fusogenic liposomes due to their special delivery pathway of membrane fusion. Additionally, human blood cells were also incubated with cationic control liposomes and free [(131)I]I(−). In these cases, iodide delivery efficiencies remained below 3%.